Describing mode of death in three major cardiac amyloidosis subtypes to improve management and survival. (3rd April 2022) - Kharoubi, Mounira; Bodez, Diane; Bézard, Mélanie; Zaroui, Amira; Galat, Arnault; Guendouz, Soulef; Gendre, Thierry; Hittinger, Luc; Attias, David; Mohty, Dania; Bergoend, Eric; Itti, Emmanuel; et al.
Abstract: Background: The three main cardiac amyloidosis (CA) types have different progression and prognosis. Little is known about the mode of death (MOD) which is commonly attributed to cardiovascular causes in CA. Improving MOD's knowledge could allow to adapt patient care. Objective: This retrospective study describes the MOD that occurred during long-term follow-up in CA patients in light-chain (AL), transthyretin hereditary (ATTRv) or wild-type (ATTRwt). Material and methods: Patients referred to and cared for, at the French referral centre for CA, Henri Mondor Hospital, Créteil between 2010 and 2016 were included. Clinical information surrounding patient deaths were investigated and centrally evaluated by two blinded clinical committees which classified MOD as cardiovascular, non-cardiovascular or unknown and sub-classified it depending on its subtype. Results: From the 566 patients included, 187 had AL, 206 ATTRv and 173 ATTRwt. During the 864 patient-year follow-up, 160 (28%) deaths occurred, with median survival time of 17.3 months (interquartile range 5.1–35.4). The most frequent MOD was cardiovascular (64%) of which worsening heart failure occurred most frequently and for which, 69% were of AL subtype, 79% ATTRv and 76% ATTRwt. Sudden death also occurred more frequently in AL subtype accounting for 29% of AL deaths. Non-cardiovascular MOD occurred in 26% of patients overall. Among these, infection was the most common non-cardiovascular MOD in any type of CA (80%). Conclusions: Mortality is high during natural course of CA and differs between subtypes. The main MOD were worsening heart failure, sudden death and infection, opening room to optimise management.